Rapid differentiation of graft Citrus sinensis with and without Xylella fastidiosa infection by mass spectrometry. (6th April 2020) - Soares, Márcio Santos; da Silva, Danielle Fernandes; Amaral, Jéssica Cristina; da Silva, Michelli Masaroli; Forim, Moacir Rossi; Rodrigues‐Filho, Edson; das Graças Fernandes da Silva, Maria Fátima; Fernandes, João Batista; Machado, Marcos Antônio; de Souza, Alessandra Alves; Martins, Carlos Henrique Gomes
Abstract : Rationale: Xylella fastidiosa causes citrus variegated chlorosis (CVC) in sweet orange trees. A diagnostic method for detecting CVC before the symptoms appear, which would inform citrus producers in advance about when the plant should be removed from the orchard, is essential for reducing pesticide application costs. Methods: Chemometrics was applied to high‐performance liquid chromatography diode array detector (HPLC‐DAD) data to evaluate the similarities and differences between the chromatographic profiles. A liquid chromatography/atmospheric pressure chemical ionization mass spectrometry selected reaction monitoring (LC/APCI‐MS‐SRM) method was developed to identify the major compounds and to determine their amounts in all samples. Results: We evaluated the effect of this bacterium on the variation in the chemical profile in citrus plants. The organs of C. sinensis grafted on C. limonia were analyzed. Chemometrics was applied to the obtained data, and two major groups were differentiated. Flavonoids were observed in one group (leaves) and coumarins in the second (roots), both at higher concentrations in the plants with CVC symptoms than in those without the symptoms and those in the negative control. The rootstocks also interfered in the metabolism of the scion. Conclusions: The developed LC/APCI‐MS‐SRM method for detecting CVC before the symptoms appear is simple and accurate. It is inexpensive, and many samples can be screened per hour using 1 mg of leaves. Knowledge of the influence of the rootstock on the chemical profile of the graft is limited. This study demonstrates the effect of the rootstock in synthesizing flavonoids and increasing its content in all parts of the graft.